Innovazione e tecnologie avanzate alla 2a Conferenza degli utenti Laser Scanner Leica Geosystems - GEOmedia, Redazione (GEOmedia, 2015)
This year the 2nd Leica Geosystems HDS User Conference, held on November 19 in Rome at the Sheraton Golf, located at the Parco dei Medici, has fueled the interest of professionals and emerging industry by disseminating and showcasing the new techniques and new instruments.